Kalwedo Sebagai Falsafah Hidup Masyarakat Kepulauan Maluku Barat Daya - Termas, Asweres A. F (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
Kalwedo, as a philosophy of life, has become the foundation for the people of the Southwest Maluku islands. The values of Kalwedo, representing the cosmological essence of Southwest Maluku, significantly impact the lives of its people. This study employs qualitative methods, with data collection techniques conducted through interviews. The results indicate that Kalwedo values have been deeply integrated into the community’s way of life and continue to be practised today. Values such as mutual assistance are embodied in the practice of living harmoniously within a diverse society. These values are regarded as part of an ancestral heritage that continues to bind the community and must be upheld in everyday life. Kalwedo is not only embraced by the people of Southwest Maluku in Maluku Province but also by those who have migrated to other parts of Indonesia. As local wisdom, Kalwedo serves as a powerful foundation for fostering harmonious coexistence with other communities in the context of diversity.